The Role Of Innovative Technologies In Preparing Young People For The Family In The Social Cooperation Of "Family, Neighborhood And Educational Institution" (Journal of Pedagogical Inventions and Practices, 2023)
The article provides ways and recommendations for improving the social cooperation of the family, neighborhood and educational institutions in the education of young people in New Uzbekistan. The use of innovative technologies in improving social cooperation and preparing young people for family is highlighted